POSSIBLE STRESS-INDUCED PHASE-TRANSITION IN O-TAS3 - DAS, K; CHUNG, M; SKOVE, MJ; TESSEMA, GX (AMERICAN PHYSICAL SOC, 1995)
We have measured the stress-strain (sigma-epsilon) relations in o-TaS3 below the charge-density-wave (CDW) transition temperature. We find a large peak in d epsilon/d sigma at a critical stress sigma(c) approximate to 0.7 GPa below 200 K. The anomaly in d epsilon/d sigma, as large as 50% and perhaps associated with a change in length, is sample and temperature dependent. We show that this anomaly is associated with previously seen anomalies in the elastic and transport properties of TaS3, and propose that there is a weakly first-order phase transition from one CDW phase to a different CDW phase at sigma(c).
Keywords: CHARGE-DENSITY-WAVE; ELASTIC ANOMALIES; ORTHORHOMBIC TAS3; PEIERLS TRANSITION; UNIAXIAL-STRAIN; YOUNG MODULUS; SHEAR-MODULUS; DEPENDENCE; CONDUCTIVITY; TEMPERATURE